Preparedness Behavior of The Destana Group in Management of Mountain Raung Eruption - Dwi Dharma Yudha; Mury Ririanty; Iken Nafikadini (State Islamic University of Sunan Ampel, 2023)
The volcanic eruption disaster in Indonesia caused economic problems in the form of loss of property, community productivity, damage to facilities and infrastructure due to volcanic materials caused by volcanic eruptions. a series of activities undertaken to anticipate disasters through organizing and through effective and efficient measures is called preparedness. The purpose of this study was to determine the preparedness behavior of the Destana group in facing the Mount Raung eruption disaster. This type of research is a case study with a qualitative approach. The main informants in this study were 5 members of the Destana group, Gunungmalang Village, Sumberjambe District, Jember Regency. Retrieval of data usingmethod flow model analysis.